Designing a Company Risk Register and Risk Monitoring System to Assist in Managing Aircraft MRO Risks - Dhamayanti, Raditia; Chudra, Glenny; Yohannis, Alfa (Jurnal Teknologi dan Manajemen Informatika, 2024)
This company specializes in maintenance, repair, and overhaul (MRO) services for aircraft. MRO activities are crucial to ensuring the safety and reliability of aircraft operations. However, these activities also involve various risks that can affect the performance and reputation of companies in multiple fields. To manage these risks effectively, a system for risk registration and monitoring has been designed for companies in the MRO industry. This paper presents the design of the Risk Register and Monitoring System, which includes the identification, assessment, and management of risks related to the activities of all existing units within companies in the MRO industry. This system is designed to provide a structured approach to risk management, which can help companies in the MRO industry manage risks across all units. The proposed system consists of several components, including automation for performing risk registers and monitoring through a website. This system allows companies in the MRO industry to assess the severity of risks, simplify risk management strategies, and streamline the risk registration process. As a result, companies in the MRO industry can minimize the impact of risks from each unit and enhance efficiency and effectiveness in risk management